Urban platform approach in Covid-19 pandemic management (case of Semarang and Yogyakarta, Indonesia) - Yudha Pracastino Heston; Bakti Setiawan; Deva Fosterharoldas Swasto (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2023)
The world population is experiencing urban life disruption since early 2020 due to the Covid-19 pandemic. In Indonesia, Semarang and Yogyakarta both are the capital cities of respective provinces, undergone the peak of pandemic twice. The first peak occurred between January and February 2021, and the second peak occurred in July 2021. The pandemic that occurred in those two cities altered the dynamics of urban social, political, and cultural dynamics. This paper attempted to discover the phenomenon of urban management in Semarang and Yogyakarta in dealing with the Covid-19 pandemic. In this study, statistical description was used by comparing indicators and investigating their relationship using urban platform approach. The study found four major variables in Semarang and Yogyakarta: the quality of the environment; collaboration and coordination among government, society, and private parties; the presence of infrastructure to deal with Covid-19; and pandemic handling in planning and implementation.